Pengembangan UMKM pada Masa Pandemi Covid-19 dan Pasca Banjir Melalui Budidaya Lele dan Jamur Tiram - Wiguna, Frans Aditia; Permana, Erwin Putera; Imron, Ilmawati Fahmi; Putri, Kharisma Eka; Damariswara, Rian; Damayanti, Susi; Hapsari, Devinsa Pinda (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Cengkok Village, Tarokan District, Kediri Regency has experienced a decrease in the quality and quantity of community income. Apart from being affected by the COVID-19 pandemic, floods often occur. In addition to material and non-material impacts, it also has a direct impact on the economic sector in the village. To improve the economic sector, the service team was moved to help find a way out of the problems of Cengkok Village, especially the economic sector. The purpose of this service is to carry out mentoring and development of MSMEs so that the community can improve the economy and the community can still run their business amidst the COVID-19 pandemic. The method used is the planning stage, the preparation stage, the activity implementation stage and the evaluation stage. The results achieved were the socialization of SME entrepreneurship, socialization of catfish empowerment, distribution of catfish seeds to some people. With the MSME Entrepreneurship Socialization, Catfish Empowerment Socialization, and the distribution of catfish seeds, it can improve the economy of the Cengkok Village community during the COVID-19 pandemic and after the flood.